Relevance and multimodal prosody: implications for L2 teaching and learning - Madella, Pauline (Frontiers in Communication, 2023)
In this paper, I build on Scott's relevance-theoretic account of contrastive stress (2021). Contrastive stress works as an extra cue to ostension in altering the salience of a particular constituent in an utterance and, as a result, the salience of one particular interpretation of that utterance. I draw on Scott’s argument that contrastive stress does not encode procedural meaning. Contrastive stress is unpredictable and, as such, it is in confounding the hearer’s expectations that it draws his attention to the accented word and prompt his search for different interpretive effects. I argue that contrastive stress is interpreted purely inferentially precisely because it is one of many pointing devices. It is to be interpreted by virtue of its interaction with other paralinguistic behaviours, all of which being different aspects of the same ostensive act of communication. This leads me to focus on the gestural nature of contrastive stress working as an act of pointing, which, as an ostensive communicative behaviour, conveys that if you look over there, you’ll know what I mean (Tomasello et al., 2007). Finally, I present the implications of analysing contrastive stress in its multimodal context – as prosodic pointing – for the teaching and learning of L2 prosodic pragmatics and the development of interpretive abilities in the L2 hearer’s mind.